2018
DOI: 10.1590/1980-5373-mr-2017-1050
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Multiple Performance Characteristics of Friction Stir Welded Joint with Grey Relational Analysis

Abstract: In the present work, multi-objective optimization of the input welding parameters influencing the quality of weld joint of AA 5052 H32 aluminium alloy by FSW process is investigated using response surface methodology and grey relational analysis. The quality of the welded joint is measured based on the higher value of tensile strength and hardness of the joint obtained by experimentation. A central composite design technique consists of 31 sets of experiments using four factors and five levels are used. Tool p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
0
7
0
1
Order By: Relevance
“…Tool geometry is one of the main process parameters that play a vital role in material flow and FSWed joint quality. The frictional heat generated during the mechanical stirring of the FSW process is correlated with the tool design [79,105,133]. The size of the weld zone (including SZ, HAZ, and TMAZ) and possible process defects are affected by tool geometry.…”
Section: Effect Of Tool Pin Geometrymentioning
confidence: 99%
“…Tool geometry is one of the main process parameters that play a vital role in material flow and FSWed joint quality. The frictional heat generated during the mechanical stirring of the FSW process is correlated with the tool design [79,105,133]. The size of the weld zone (including SZ, HAZ, and TMAZ) and possible process defects are affected by tool geometry.…”
Section: Effect Of Tool Pin Geometrymentioning
confidence: 99%
“…Increasing in tilt angle results in increasing the UTS to reach the maximum value at 3 • and 30 mm/min, and then gradually decreases as these two parameters increase. Increasing the tilt angle of the welding tool leads to an increase in the vertical force and torque, this may lead to an increase in the contact between the tool and the workpiece and then the highest heat inputs are achieved which causes a thermal softening of the deformed material and an increase in the flow of downward materials, where the restoration of grains are obtained in stir zone that occurs in conjunction with the deformation, and this process is called dynamic recrystallization, which leads to the grain refinement during welding [50]. Fig.…”
Section: Prediction Of Fsw Process Parametersmentioning
confidence: 99%
“…Prevention of defects formation during FSP is very important to produce a quality workpiece. Shamsudeen et al [17] demonstrated the influence of tool shape on microstructural properties and tensile strength of AA 5052 H32 aluminum alloy. Govindaraju et al [18] studied the influence of FSP with several heat treatment conditions on the microstructural evolutions of AZ91.…”
Section: Introductionmentioning
confidence: 99%